CLINICAL AND LABORATORY SIGNIFICANCE OF BRUCELLOSIS AND OPTIMIZATION OF TREATMENT (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
Brucellosis is characterized by a polymorphic clinical course and a wide spectrum of manifestations, ranging from acute febrile illness to chronic debilitating forms with multisystem involvement. The causative agents, bacteria of the genus Brucella, are facultative intracellular pathogens capable of long-term persistence within macrophages and other cells of the reticuloendothelial system. This intracellular localization allows the pathogen to evade immune surveillance and contributes to chronic inflammation, relapses, and resistance to therapy. One of the key pathogenetic mechanisms of brucellosis is the development of a systemic inflammatory response.